1994
DOI: 10.1046/j.1471-4159.1994.63020535.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Calcium Influx in Muscarinic Cholinergic Regulation of Phospholipase C in Cerebellar Granule Cells

Abstract: Inositol phosphate accumulation on carbachol stimulation of rat cerebellar granule cells shows a marked dependence on factors affecting cytosolic Ca2+ concentration ([Ca2+]c). After 5 min, potassium depolarisation caused a modest accumulation of inositol phosphates but augmented the response to carbachol by a factor of 2–3. These effects of potassium were dependent on an extracellular source of calcium and could be partially blocked by specific (nifedipine) and nonspecific (verapamil) calcium channel blockers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 23 publications
8
31
2
Order By: Relevance
“…This suggests that Ca 2ϩ alone is not sufficient for phospholipase C-␤ activation but an additional receptor-associated mechanism is also required. An enhancement of the maximum IP 3 production by elevated [Ca 2ϩ ] i has been previously shown for muscarinic receptors (25,26). However, there has not been any indication of any receptor-operated pathway that would enhance the primary IP 3 response; on the contrary, the potentiating effect of Ca 2ϩ on IP 3 production has been seen after activation of voltage-sensitive Ca 2ϩ channels (25) or artificial regulation of [Ca 2ϩ ] i in permeabilized cells (26).…”
Section: Discussionmentioning
confidence: 83%
“…This suggests that Ca 2ϩ alone is not sufficient for phospholipase C-␤ activation but an additional receptor-associated mechanism is also required. An enhancement of the maximum IP 3 production by elevated [Ca 2ϩ ] i has been previously shown for muscarinic receptors (25,26). However, there has not been any indication of any receptor-operated pathway that would enhance the primary IP 3 response; on the contrary, the potentiating effect of Ca 2ϩ on IP 3 production has been seen after activation of voltage-sensitive Ca 2ϩ channels (25) or artificial regulation of [Ca 2ϩ ] i in permeabilized cells (26).…”
Section: Discussionmentioning
confidence: 83%
“…Because the increase in BDNF production by AMPAR stimulation was augmented by costimulation of mGluR (Yuzaki et al, 1994) and IP 3 production by G-protein-coupled receptors was greatly increased by costimulation of AMPAR (Baird et al, 1991;del Rio et al, 1994;Nash et al, 2004), it is plausible that AMPAR and mGluR cooperatively activate the signaling pathway for IP 3 R-mediated BDNF production. In contrast, it remains unknown how the BDNF produced in cerebellar granule cells regulates the dendritic morphology of Purkinje cells intercellularly.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether IP 3 R1 actually functions in granule cells, we stimulated granule cells with trans-(Ϯ)-1-amino-1,3-cyclopentanedicarboxylic acid (ACPD), an agonist for group 1 metabotropic glutamate receptors that are linked to the phospholipase C (PLC)-IP 3 production pathway, and measured Ca 2ϩ changes. To maximize the IP 3 -induced Ca 2ϩ release, we exposed the cells to high K ϩ before mGluR stimulation (del Rio et al, 1994). As shown in Figure 5B, a Ca 2ϩ transient was observed in WT cerebellar granule cells in response to trans-ACPD (top panel), but no Ca 2ϩ transient, only a slight increase in basal Ca 2ϩ level, was observed in the IP 3 R1 KO cerebellar granule cells.…”
Section: Abnormal Ca 2؉ Signaling In Ip 3 R1 Ko Cerebellar Granule Cementioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical studies have shown that the activity of PLC enzymes including the PLCβ family is Ca 2+ dependent (Biddlecome et al, 1996;Rebecchi and Pentyala, 2000). In rat cultured cerebellar granule cells, carbachol-stimulated inositol phosphate accumulation, which reflects PLC activity, was shown to be highly sensitive to small changes in [Ca 2+ ] i (del Rio et al, 1994). An electrophysiological study using exogenous TRPC6 channel as a biosensor for the PLC product diacylglycerol in our laboratory demonstrated that PLCβ1 activation driven by muscarinic receptors (Fig.…”
Section: Discussionmentioning
confidence: 99%